Coverage and Factors Related to Early Breastfeeding Initiation in Nusa Tenggara - Haerawati Idris; Asmaripa Ainy; Desri Maulina; Nurmalia Ermi (Journal of Agromedicine and Medical Sciences, 2023)
The Infant Mortality Rate (IMR) is an indicator to assess the degree of public health in a country. One of the efforts to reduce infant mortality is through the promotion of breastfeeding practices. The purpose of this study is to analyze the scope and determinants of IMD implementation in Nusa Tenggara. The design of this study uses a cross-sectional approach. This study analyzed secondary data from the 2017 Indonesian Health Demographic Survey (IDHS). The sample used in this study was women of childbearing age (15-49 years) who have given birth in the last 2 years, have their last child under 6 months old who is still alive, and live with their child with with a total of 603 respondents. Binary logistic regression was used to analyze the data. The results of this study show that 70.8% of respondents carried out the Early Breastfeeding Initiation. Normal delivery has a relationship with the implementation of early breastfeeding initiation in Nusa Tenggara. Socialization and education regarding normal childbirth need to be optimized as an effort to increase early initiation of breastfeeding. Keywords: infant; female; breast feeding; Indonesia; health survey